Michael-addisiereaksies van gekonjugeerde fosfoniumyliede - Bredenkamp, M. W.(Martin William) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc.) -- Universiteit van Stellenbosch, 1980..